Green product purchase intention among university students: Extending the theory of planned behaviour - Chuah, Chin Wei; Ali, Juha; Ali, Mumtaz (2017)
The present research attempts to investigate the use of green product among university students. The theory of plan behaviour underpins the research framework of this study. Specifically, this study aims to investigate the effect of attitude, subjective norms and perceived behavioural control on intention to purchase green product. In addition to that, environmental concern is incorporated in the model as the antecedents influencing one’s attitude towards green product.